Discourses at the Communion on Fridays - Kierkegaard, Søren, 1813-1855 (Indiana series in the philosophy of religion., 2011)
Sr̜en Kierkegaard's 13 communion discourses constitute a distinct genre among the various forms of religious writing composed by Kierkegaard. Originally published at different times and places, Kierkegaard himself believed that these discourses served as a unifying element in his work and were crucial for understanding his religious thought and philosophy as a whole. Written in an intensely personal liturgical context, the communion discourses prepare the reader for participation in this rite by emphasizing the appropriate posture for forgiveness of sins and confession.